Venous infarction mimicking top of basilar syndrome; An uncommon complication of adult influenza infection. (March 2017) - Cho, Soo Hyun; Lee, Kyung Mi; Kim, Bum Joon; Yi, Jae Hong; Noh, Kyung Chul; Kim, Eui Jong; Rhee, Hak Young; Park, Key-Chung
Highlights: Influenza increases the risk of ischemic and hemorrhagic stroke. Influenza viruses may promote development of massive venous thrombotic events. Venous infarction can be an uncommon complication of adult influenza infection. Abstract: Influenza infection increases the risk of ischemic stroke. Here, we represent a case of a 32 year-old female who presented with acutely developed altered mental status after influenza A infection. The clinical manifestation and initial lesion on brain DWI mimicked top of basilar syndrome, but without an arterial occlusion or stenosis. Follow-up neuro imaging analysis suggested cerebral venous infarction. It is valuable to report this case of venous infarction in a healthy young adult, as an uncommon complication of adult influenza infection.